2017
DOI: 10.7774/cevr.2017.6.2.83
|View full text |Cite
|
Sign up to set email alerts
|

The significance of avian influenza virus mouse-adaptation and its application in characterizing the efficacy of new vaccines and therapeutic agents

Abstract: Due to the increased frequency of interspecies transmission of avian influenza viruses, studies designed to identify the molecular determinants that could lead to an expansion of the host range have been increased. A variety of mouse-based mammalian-adaptation studies of avian influenza viruses have provided insight into the genetic alterations of various avian influenza subtypes that may contribute to the generation of a pandemic virus. To date, the studies have focused on avian influenza subtypes H5, H6, H7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
(178 reference statements)
0
4
0
Order By: Relevance
“…PB2 D701N substitution also conferred aerosol transmission in guinea pigs as a substitute for the lack of PB2-E627K [ 43 ] and it was primarily found in a duck H5N1 virus that was highly pathogenic to mice [ 90 , 91 ]. Interestingly, the two well-studied mammalian adaptive mutations, E627K and D701N, do not seem to be simultaneously induced in the PB2 gene of the adapted viruses [ 92 , 93 ]. A study on reassortment between HPAI avian H5N1 virus with genes from pandemic 2009 H1N1 virus has found that the PA and NS genes conferred respiratory droplet transmissibility to the H5N1 virus in guinea pigs and the NA and M genes of the human virus also assisted in transmission of H5N1 through respiratory droplets in this animal model [ 39 ].…”
Section: Avian Influenza Virus Transmission In Various Mammalsmentioning
confidence: 99%
“…PB2 D701N substitution also conferred aerosol transmission in guinea pigs as a substitute for the lack of PB2-E627K [ 43 ] and it was primarily found in a duck H5N1 virus that was highly pathogenic to mice [ 90 , 91 ]. Interestingly, the two well-studied mammalian adaptive mutations, E627K and D701N, do not seem to be simultaneously induced in the PB2 gene of the adapted viruses [ 92 , 93 ]. A study on reassortment between HPAI avian H5N1 virus with genes from pandemic 2009 H1N1 virus has found that the PA and NS genes conferred respiratory droplet transmissibility to the H5N1 virus in guinea pigs and the NA and M genes of the human virus also assisted in transmission of H5N1 through respiratory droplets in this animal model [ 39 ].…”
Section: Avian Influenza Virus Transmission In Various Mammalsmentioning
confidence: 99%
“…Many human and avian IAVs have also been adapted to elicit weight loss and lethal disease in mouse models. These models have been created to evaluate efficacy of vaccines and therapeutic agents against influenza virus strains that do not cause measurable clinical signs in mice (Choi et al, 2017;Majde et al, 2007). These examples, among others, demonstrate the value of manipulating viral strains to produce measurable signs of morbidity (notably weight loss and lethal outcome) in certain animal models.…”
Section: Requires Immunodeficient Mouse Strains or Transient Immunosu...mentioning
confidence: 99%
“…Rather, they exhibit loss of body weight, reduced respiratory function, and decreased locomotive activity. As human pathogens often replicate less efficiently in mice, it is frequently necessary to use mouse-adapted viral strains selected for increased replication and disease in inbred mouse strains, which may or may not replicate disease symptoms seen in humans [4]. The most commonly used parameters for viral infection intensity in mice are changes in body weight and survival rate.…”
Section: The Laboratory Mouse In Viral Disease Researchmentioning
confidence: 99%